2014
DOI: 10.1095/biolreprod.114.122168
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Pannexin-1 Promoter in the Rat Epididymis1

Abstract: Pannexins (PANXs) are channel-forming proteins implicated in cellular communication through the secretion of biomolecules, such as ATP and glutamate. PANX1 and PANX3 are expressed in the male rat reproductive tract and their levels are regulated by androgens in the epididymis. There is currently no information on the regulation of the Panx1 promoter. The objective of the present study was to characterize the Panx1 promoter in order to understand its regulation in the epididymis. RNA ligase-mediated rapid ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 65 publications
1
19
0
Order By: Relevance
“…To explore the functionality of Panx1 channels in adipocytes we performed experiments with cultured 3T3-L1 adipocytes and primary adipocytes isolated from wild-type or Panx1 KO mice, using known activators of Panx1 channel function [28,30,32] . We found that Panx1 expression in 3T3-L1 adipocytes is induced by insulin ( Figure S1B ), which is in line with reports that cAMP response elements play a role in transcriptional regulation of Panx1 [46] . First indications for a functional role of Panx1 in adipocytes came from experiments where treatment of 3T3-L1 adipocytes with the α-adrenergic receptor agonist phenylephrine (PE) caused a dose-dependent increase in the uptake of YO-PRO ® , a green-fluorescent dye that can enter cells via open Panx1 channels [28,47] ( Figure 1 A).…”
Section: Resultssupporting
confidence: 91%
“…To explore the functionality of Panx1 channels in adipocytes we performed experiments with cultured 3T3-L1 adipocytes and primary adipocytes isolated from wild-type or Panx1 KO mice, using known activators of Panx1 channel function [28,30,32] . We found that Panx1 expression in 3T3-L1 adipocytes is induced by insulin ( Figure S1B ), which is in line with reports that cAMP response elements play a role in transcriptional regulation of Panx1 [46] . First indications for a functional role of Panx1 in adipocytes came from experiments where treatment of 3T3-L1 adipocytes with the α-adrenergic receptor agonist phenylephrine (PE) caused a dose-dependent increase in the uptake of YO-PRO ® , a green-fluorescent dye that can enter cells via open Panx1 channels [28,47] ( Figure 1 A).…”
Section: Resultssupporting
confidence: 91%
“…and reverse primer, one of them being biotinylated (49). Information about PCR and sequencing primers and the sequence-to-analyze is summarized in Table 1 (11). Quantification of the DNA methylation status of the Panx1 was performed on a PyromarkQ24 system (Qiagen) as described by Freitag et al (15).…”
Section: Methodsmentioning
confidence: 99%
“…Jiang et al reported increases in expression of Panx1 in mouse models of inducible stroke, which are associated with increased TNF-induced inflammation and tissue injury (Bokhari et al, 2014; Jiang et al, 2012; Liu and McCullough, 2011; Tuttolomondo et al, 2009; Tuttolomondo et al, 2014). In silico analysis has highlighted a number of transcriptional start sites within the rat Panx1 sequence, with binding sites for several transcription factors including CREB and ETV4 as well as factors downstream from IL-6 that have been identified (Dufresne and Cyr, 2014). Our RNA-seq data highlighted that TNF upregulates all NFκβ genes in HUVECs.…”
Section: Discussionmentioning
confidence: 99%